Earlier Alcohol Use Onset Predicts Poorer Neuropsychological Functioning in Young Adults. (30th October 2017) - Nguyen‐Louie, Tam T.; Matt, Georg E.; Jacobus, Joanna; Li, Irene; Cota, Claudia; Castro, Norma; Tapert, Susan F.
Abstract : Background: Neurodevelopment may be shaped by environmental factors such as alcohol intake. Over 20% of U.S. high school students begin drinking before age 14, and those who initiated drinking before age 14 are 4 times more likely to develop psychosocial, psychiatric, and substance use difficulties than those who began drinking after turning 20. Little is known, however, about how the age of alcohol use onset influences brain development. Methods: This study prospectively examined the effects of alcohol use onset age on neurocognitive functioning in healthy adolescent drinkers ( N  = 215). Youth were administered a neuropsychological battery before substance use initiation ( M  = 13.6 years, SD = 0.8) and on average 6.8 years later ( M  = 20.2 years, SD = 1.5). Hierarchical linear regressions examined if earlier ages of onset for first and regular (i.e., weekly) alcohol use adversely influenced neurocognition, above and beyond baseline neurocognition, substance use severity, and familial and social environment factors. Results: As hypothesized, an earlier age of first drinking onset (AFDO) predicted poorer performance in the domains of psychomotor speed and visual attention ( p s<0.05, N  =   215) and an earlier age of weekly drinking onset (AWDO) predicted poorer performances on tests of cognitive inhibition and working memory, controlling for baseline neuropsychological performance, drinking duration, and past‐year marijuana use ( p s<0.05, N  =   127). No relationship between AFDO and AWDO was found with verbal learning and memory and visuospatial ability. Conclusions: This is the first study to assess the association between age of adolescent drinking onset and neurocognitive performance using a comprehensive test battery. This study suggests that early onset of drinking increases risk for alcohol‐related neurocognitive vulnerabilities and that initiation of any or weekly alcohol use at younger ages appears to be a risk factor for poorer subsequent neuropsychological functioning. Findings have important implications for public policies related to the legal drinking age and prevention programming. Further studies are needed to replicate these preliminary findings and better understand mediating processes and moderating conditions. Abstract : Early onset of any and weekly alcohol use may increase risk for poorer subsequent cognitive functioning, even after accounting for pre‐drinking neuropsychological performance. An earlier age of first drinking onset predicts poorer performances in psychomotor speed and visual attention ( N  = 215) and an earlier age of weekly drinking onset predicts poorer performances in cognitive inhibition and working memory, controlling for baseline performance, lifetime drinking duration, and past‐year marijuana use ( N  = 127, p s < 0.05).